The development of global education in Malaysia: Strategies for internationalization - Mohamad, Mohamad Hanapi; Ghazali, Zahiruddin; Kassim, Mohd Shah (Malaysian Institute of Management, 2003)
The globalization of the economy and society has had its impact on and has been influenced by research and education.In the ease of Malaysia, the policy of liberalization and democratization of education sees a sudden upsurge of foreign students studying in Malaysia as from 1996 when the government introduced the Higher Education Act. Terms such as "international education" and "global education" have been the expression of this development.However, to really become a major player, Malaysia essentially needs to acquire global competencies, either in the curriculum, administrative easiness. or pricing in order to make its location a strategic choice for post-secondary education.The globalization of markets and competition, rapid technological changes, and changing relationship between states and firms require different approaches from those traditionally assumed.This paper proposes the development of a coherent global education model of higher education, constructed on eclectic-locational approach rather than a multidisciplinary approach.